Olfactory behavioural and neural responses of planktivorous lacustrine sockeye salmon (Oncorhynchus nerka) to prey odours. Issue 1 (10th June 2022) - Konishi, Junnosuke; Abe, Takashi; Ogihara, Atsushi; Adachi, Daisuke; Denboh, Takashi; Kudo, Hideaki
Abstract: Fish use a variety of sensory systems when foraging. Salmonids are generally considered visual feeders. However, some species feed on zooplanktons under dark conditions, suggesting they also detect prey using nonvisual cues. Under experimental conditions, hatchery‐reared rainbow trout ( Oncorhynchus mykiss ) have been shown to use olfaction when searching for food pellets, but olfactory foraging has not been documented in wild salmonids. In the present study, to examine their behavioural response and neural activity in the olfactory nervous system using c‐fos expression as a neural molecular marker, immature wild‐caught lacustrine sockeye salmon ( Oncorhynchus nerka ) in a flow‐through aquarium were exposed to zooplanktons ( Daphnia spp.) extract including zooplanktons odorant and to dimethyl sulfide. The salmon exposed to zooplanktons odour increased their total swimming distance and time, numbers of turns and ascents, and c‐fos expression in the olfactory bulb, suggesting that they can detect zooplanktons extract to locate prey in the laboratory experiments. However, no response was seen in those exposed to dimethyl sulfide. The results of this study suggest that prey odour may serve as a chemosensory cue for wild immature salmonids.